Observing population changes of thrips (Thysanoptera) species damaging forced pepper and their natural enemies - Molnár, A.; Pap, Z.; Fail, J. (International Journal of Horticultural Science, 2008)
By the strengthening of environmental protection and food safety efforts in Hungary, integrated and especially biological pest control methods should increasingly put forward, for which a solid knowledge on the life course and efficiency of natural enemies applied against certain pests is necessary. Pepper has distinguished significance in domestic vegetable forcing, and the profitability of production is determined primarily by the efficiency of the control of thrips pests. This is why we attached great importance to study what results may be expected by introducing arthropod predators (Amblyseius cucumeris, Orius laevigatus) to control thrips species under domestic conditions on rock wool in a long vegetation period pepper culture. We also liked to find out what kind of role the cultivars play in the change of phytophagous and zoophagous populations. The A. cucumeris predatory mite introduced in late January proved to be effective in controlling thrips pests until mid-April. Despite repeated introductions, the predatory bug O. laevigatus (Heteroptera: Anthocoridae) did not proliferate. Among the three pepper cultivars (Hó, Keceli, Titán) grown at Ráckeve, thrips species proliferated in the highest number on cultivar 'Hó', while the population of predatory mites was lowest on the cultivar 'Titan', compared to the other two cultivars.